Pre-conscription training in the education system in the Eurasian space - Antonov Александр (Рroblems of engineering and professional education, 2023)
The article analyzes the programs of pre-conscription training of students in the education system in Russia, the Republic of Belarus and the Republic of Kazakhstan. Negative and positive sides are defined. Further development paths are outlined.